Silicon visions : (Prentice Hall Press, 1986)
Japan is developing a number of high technology centers, borrowing elements of similar efforts in the United States (Silicon Valley, North Carolina's Research Triangle Park, Boston's Route 128, etc.). Tatsuno's analogy of castle town development in pre-modern Japan is a bit overdone, but he does present a comprehensive picture of the centers and of research in progress or planned for the future. He concludes with a thoughtful analysis of the Japanese plan and accomplishments, and of comparable projects in the United States. This informed overview belongs in most subject collections.